Guerra e tecnica nell’epoca weimariana: il contributo di Oswald Spengler ed Ernst Jünger - Prunotto, Pietro (Mechane, 2023)
This article analyses the influence of the First World War on the philosophical analysis of technology. To this end, the Conservative Revolution, a phenomenon that originated in Germany during the Weimar era, will be used as a case study, particularly regarding its most important thinkers, namely Oswald Spengler and Ernst Jünger. In the comparison and analysis of these two authors, some new characteristics of technique emerge that will become the starting point of many later authors.